Desenvolvimento de método para determinação de resíduos de pesticidas na planta medicinal Transagem (Plantago major L.) utilizando as técnicas de DMFS e CLAE-UV/DAD - Santos, Érica Silvia dos (2012)
The therapeutic use of medicinal plants is based on family tradition and became widespread in folk medicine. Yet there is a guarantee for the vast majority of products sold on the quality and effectiveness, since medicinal plants are subject to various types of contamination, such as pesticide residues. These chemicals are used to control and combat pests and weeds, but are potentially toxic to humans. As a result, this study aims to develop techniques based on the method of the matrix solid-phase dispersion (MSPD) and high performance liquid chromatography with UV detection with a photodiode array to determine pesticide residues kresoxim-methyl, and clofentezine and flumetralina in samples of dried and fresh transagem (Plantago major L.). The method of the matrix solid-phase dispersion was carried out using samples dried, testing different adsorbents (neutral alumina, Florisil ®, silica, C18 and Basolite®), in ratio matrix / sorbent 1:1 (m / m). The optimum recoveries for pesticide analysis HPLC-UV/DAD were obtained with silica (adsorbent), using a volume of 20 mL of dichloromethane with average recovery ranging from 45.5 to 90.3%, and coefficients variation in the range 6.1 to 18.5% for concentrations of 1.0, 1.5 and 2.0 μg g-1. Correlation coefficients between 0.9992 and 0.9997 were obtained for a concentration range between 0.2 and 5.0 μg g-1. The limits of detection and quantification were in the range 0.60 to 0,90 μg g-1 and 1.0 μg g-1, respectively. Tests were also made with the recovery of pesticides using the dried plant using the adsorbing aminopropyl and coordination polymer [Zn(BDC)(H2O)2]n. Were carried out by the analysis technique HPLC-UV/DAD with the plant in nature, using silica adsorbent with recovery values of pesticides in the range 78.3 to 110.1% and coefficients of variation between 9.9 and 15.6% for the concentration level of 2.0 μg g-1.